ZZ production in e(+) e(-) interactions at root s=183-209 GeV - Abdallah, J; Abreu, P; Adam, W; Adzic, P; Albrecht, T; Alderweireld, T; Alemany-Fernandez, R; Allmendinger, T; Allport, P; Amaldi, U; Amapane, N; Amato, S; et al. (2003)
Measurements of on-shell ZZ production are described, using data from the DELPHI experiment at LEP in e+e- collisions at centre-of-mass energies between 183 and 209 GeV, corresponding to an integrated luminosity of about 665 pb-1. Results obtained in each of the final states qq̄qq̄, νν̄qq̄, μ+μ -qq̄, e+e-qq̄, τ -τ-qq̄, l+l-l +l-, and νν̄+l- (with l = e,μ) are presented. The measured production cross-sections are consistent with the Standard Model expectations. These results update and supersede those already published at 183 and 189 GeV.